A mathematical model of the motion of the screening surface under the conditions of its impact vibration action - Zaselskyi , V.Y.; Popolov , D.V. (Theory and Practice of Metallurgy, 2023)
The article presents an integrated approach to solving the actual problem of increasing the efficiency of screening charge materials, which is important for metallurgical production. The aim of the research is to develop a mathematical model of the motion of a loosely stacked screening surface under the conditions of its vibration and impact action. To achieve this goal, we have used a step-by-step systematic analysis of the theoretical study of of the motion of the sieving surface, which is considered as a material point whose motion limited to a certain interval, and is divided into six characteristic stages, each of which is analyzed separately. As a result of the study, the following were developed a differential equation of motion of the sowing surface and obtained dependencies that allow us to describe its motion in different dynamic states, taking into account the forces of inertia, elastic deformation, gravity, and friction. The conditions under which resonance occurs and the intensity of the sieve tossing increases. This allows minimizing the phenomenon of clogging of the holes of the sieving surface, which, in turn, increases the efficiency of the turn, increases the efficiency of the screening process. The scientific novelty of the study is the development of a new mathematical model that describes the movement of a loosely of a loosely laid sowing surface under the conditions of its vibration and impact action. This allows us to for the first time to study in detail the processes occurring during screening, and to determine the optimal conditions for reducing clogging of the seeding surface holes. The results of this study can be used to improve the process of preparing iron-containing raw materials for remelting, which is an urgent task for the metallurgical industry. The application of the developed mathematical model will increase the efficiency of screening out fines and fractions, reduce clogging of the holes of the screening surface, which will improve the overall quality of metallurgical processes. This, in turn, will help save resources and reduce production costs.